The Standardization of Halal Tourism Management in West Nusa Tenggara - Abdul Kadir Jaelani (Faculty of Law, Universitas Pekalongan, 2021)
This research aims at explaining the standardization of halal tourism management in West Nusa Tenggara. The result shows that the standardization of halal tourism management through Regional Regulation Number 2 of 2016 on Halal Tourism has not solved the problems of regional tourism such as good environmental maintenance from the increasingly damaged biology resource crisis, the deforestation, the limited water resources, soil erosion, sedimentation, abrasion on the cost, coral reef damage, littering 53% or about 250 ton plastic waste every day. Even, this regional regulation is in contrary to the higher laws and religious nuances.